PIV experimental study on the phase change behavior of phase change material with partial filling of metal foam inside a cavity during melting. (15th May 2022) - Liu, Aihua; Lin, Junjiang; Zhuang, Yijie
Highlights: Phase change behavior of PCM with partial porous filling is experimentally investigated. Four different configurations with and without partial porous filling are designed. The velocity fields in the liquid PCM are measured with PIV technique. Reveal that four regimes exist in the melting process of PCM. The lower porous filling should be chosen as the optimum porous filling strategy. Abstract: The present experimental research aims to address the transient phase change performance of phase change material (PCM) with partial filling of metal foam inside a cavity heated from one vertical side. n-octadecane is used as the PCM and copper metal foam is employed to enhance the thermal response of PCM. Four different porous configurations with non-porous filling (pure PCM), lower left porous filling, lower porous filling and left porous filling are designed. The velocity fields in the liquid PCM are measured with particle image velocimetry (PIV) technique, while the temperature fields within and outside the test cell are measured by thermocouples and infrared thermography technology, respectively. The liquid fraction and the solid-liquid interface shape are also reported. The experimental results reveal that four regimes exist in the melting process of PCM. The metal foam can enhance the thermal conduction in porous area but suppress the thermal convection in pure PCM area. The peak of phase change interface appears on the horizontal boundary between pure PCM and porous areas due to the permeability difference and thermal resistance. Additionally, it is found that the lower porous filling can effectively accelerate the melting in 'shrinking solid' regime because of metal foam participation in the whole melting process, hence this configuration finishes melting firstly. The lower porous filling should be chosen as the optimum porous filling strategy with higher thermal performance in terms of the total melting time and local Nusselt number. The detailed visualization melting evolvement results can be helpful to validate numerical model and make the optimal partial filling strategy of porous media in the applications of latent heat thermal energy storage (LHTES).